High‐latitude dust in the Earth system. (4th June 2016) - Bullard, Joanna E.; Baddock, Matthew; Bradwell, Tom; Crusius, John; Darlington, Eleanor; Gaiero, Diego; Gassó, Santiago; Gisladottir, Gudrun; Hodgkins, Richard; McCulloch, Robert; McKenna‐Neuman, Cheryl; Mockford, Tom; et al.
Abstract: Natural dust is often associated with hot, subtropical deserts, but significant dust events have been reported from cold, high latitudes. This review synthesizes current understanding of high‐latitude (≥50°N and ≥40°S) dust source geography and dynamics and provides a prospectus for future research on the topic. Although the fundamental processes controlling aeolian dust emissions in high latitudes are essentially the same as in temperate regions, there are additional processes specific to or enhanced in cold regions. These include low temperatures, humidity, strong winds, permafrost and niveo‐aeolian processes all of which can affect the efficiency of dust emission and distribution of sediments. Dust deposition at high latitudes can provide nutrients to the marine system, specifically by contributing iron to high‐nutrient, low‐chlorophyll oceans; it also affects ice albedo and melt rates. There have been no attempts to quantify systematically the expanse, characteristics, or dynamics of high‐latitude dust sources. To address this, we identify and compare the main sources and drivers of dust emissions in the Northern (Alaska, Canada, Greenland, and Iceland) and Southern (Antarctica, New Zealand, and Patagonia) Hemispheres. The scarcity of year‐round observations and limitations of satellite remote sensing data at high latitudes are discussed. It is estimated that under contemporary conditions high‐latitude sources cover >500, 000 km 2 and contribute at least 80–100 Tg yr −1 of dust to the Earth system (~5% of the global dust budget); both are projected to increase under future climate change scenarios. Key Points: High‐latitude dust sources are located in paraglacial regions ≥50°N and ≥40°S Large gaps exist in our understanding of some of the basic characteristics of high‐latitude dust sources High‐latitude sources of dust contribute at least 5% of the global dust budget